ANALISIS PERAN PARIWISATA PANTAI CAMPLONG TERHADAP KESEJAHTERAAN MASYARAKAT LOKAL - Sahir -; Kurniyati Indahsari; Henny Oktavianti (MediaTrend, 2014)
The pupose of this research was to determine how the role of Campylong on thewelfare of local communities. This research used qualitative approach and descriptivedata, both of primary data and secondary data. The first they are observations andinterviews. Secondary data are BPS Sampang, Disbudparpora, District Camplong andEast Java BPS.The result showed that the presence of Camplong is provide impact and benefitsfor the serrounding communities who are directly involved in activities suc as tourismcan provide and increase the income of surrounding community, providing businessopportunities for the local population, provide employment, improve the quality ofhuman resources and also provide benefits in introducing regional culture. In addition,the Camplong also create prosperity for the people directly involved in tourismactivities. Evident when researcher calculate income communities and most of thesurrounding community has reached welfare or income is above the poverty line. Whilea small portion of the surrounding communities who are directly involve is still notprosper due to lack of numbers of visitors and so on, so that their income was notoptimal or still below the poverty line. While the surrounding communities who are notdirectly involved in tourism activities is still not feeling great benefits with the tour.